Pertumbuhan larva kumbang tanduk (Oryctes rhinoceros L.) pada berbagai media tumbuh tanaman Famili Arecaceae - Hafiz Fauzana; Ustadi Ustadi (Jurnal Entomologi Indonesia, 2020)
Rhinoceros beetle (Oryctes rhinoceros) is the main pest of various crops, especially Arecaceae. This research aims to obtain the best growing media of the Arecaceae for the growth of O. rhinoceros larvae. This research expected was designed using a complete randomized design with 5 treatments and 4 replications. The treatment used was different media growth from Arecaceae plants namely palm oil, coconut, sago, and areca, chopped stem, as well as topsoil as control. Parameters measured included individual weight gain of larvae, larval length, a width of O. rhinoceros larvae, with supporting data of soil temperature and humidity, and chemical analysis of organic matter (C-Organic, total N, P-total, and K-Total). The results of the study showed that the growing media of oil palm stem chopped tends to be the most suitable for the growth of O. rhinoceros larvae in case of individual weight increased of larvae (8,8 ± 0,38 g), the length size of larvae (6,15 ± 0,82 cm), and the body width of larvae (1,05 ± 1 cm), and followed by the less and less suitable of the following media growing from chopped stem: coconut, sago, and areca. Thus, oil palms supports the growth of O. rhinoceros more than coconut. This information is important for pest management in smallholders oil palm plantation where oil palms are usually planted along with coconut plants.